Ranking the VIR collection of maize (Zea mays L.) according to the traits valuable for breeding in the soil and climate environments of the Republic of Belarus - Ye. M. Govor; E. B. Khatefov (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the maize collection held by VIR requires a comprehensive assessment of all its traits of breeding value. The soil and climate conditions in Gomel Province, Republic of Belarus, are characterized by insufficient levels of rainfall and total active temperatures during the initial stages of organogenesis in maize plants, therefore it is important to take into account these specific climate features when selecting the source material for breeding.Materials and methods. Sixty-seven maize accessions from the VIR collection (reproductions of 1975–1980) were phenotyped according to major traits of breeding value. The experiments were performed in 2016 and 2017 in two replications.Results. Analyzing the duration of the period from emergence to cob flowering helped to identify 61% of the accessions that were classified into early- and mid-ripening groups; 55% that were severely damaged by Ostrinia nubilalis Hbn., and 45% showing weak and medium damage; 7.5% severely affected by Ustilago maydis (DC.) Corda, and 67% without damage. Maize lines were identified (YuV24, CM7, TF907, Fc1554) with low harvesting moisture content in grain (up to 20%), lines (TF907, TF903, TF901, CM25, YuV24) with high grain yield per cob (80%), and lines (P346, Fc1554, Q184, TF903, F676) prone to the formation of two ears.Conclusion. The research results proved the efficiency of the assessment of maize accessions from VIR for traits of breeding value in the water- and heatdeficient environments of Belarus in order to use them as source material in hybrid breeding.